2011
DOI: 10.1124/jpet.111.181891
|View full text |Cite
|
Sign up to set email alerts
|

Anacardic Acid (6-Pentadecylsalicylic Acid) Inhibits Tumor Angiogenesis by Targeting Src/FAK/Rho GTPases Signaling Pathway

Abstract: Anacardic acid (6-pentadecylsalicylic acid), a natural inhibitor of histone acetyltransferase from Amphipterygium adstringens, has been shown to have anti-inflammatory, anticancer, antioxidative, and antimicrobial functions. However, whether this salicylic acid could block angiogenesis has not been elucidated to date. Here, we postulate that anacardic acid affects multiple steps of tumor angiogenesis to contribute to tumor inhibition. In this study, we found that vascular endothelial growth factor (VEGF)-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 47 publications
0
43
1
Order By: Relevance
“…As we have discussed above, AA plays a diverse role in various cancers and acts through multiple pathways. For example, the potent inhibitory activity of AA on VEGF-stimulated migration, capillary structure formation, attachment and paxillin activation in endothelial cells has previously been reported [11]. However, in our study, AA was found to promote the expression of VEGF mRNA and protein in ovarian cancer cells Therefore, we speculate that AA may promote migration and invasion in ovarian cancer via the VEGF pathway.…”
Section: Discussioncontrasting
confidence: 61%
“…As we have discussed above, AA plays a diverse role in various cancers and acts through multiple pathways. For example, the potent inhibitory activity of AA on VEGF-stimulated migration, capillary structure formation, attachment and paxillin activation in endothelial cells has previously been reported [11]. However, in our study, AA was found to promote the expression of VEGF mRNA and protein in ovarian cancer cells Therefore, we speculate that AA may promote migration and invasion in ovarian cancer via the VEGF pathway.…”
Section: Discussioncontrasting
confidence: 61%
“…Src and VEGF cooperation can be targeted by the Src-specific inhibitor dasatinib (50) and several other pharmacological compounds (35, 5358). Of strong interest for clinical applications, in vivo studies have also demonstrated that Src inhibition is able to provoke decreased tumoral xenograft growth by reducing angiogenesis (50, 56). …”
Section: Src and Prostate Cancer Progressionmentioning
confidence: 99%
“…Garcinol and anacardic acid are both EP300 and KAT2B HAT inhibitors. Antitumor activities of all the three molecules in a wide variety of cancers include interefernce with different cell signaling pathways, like cell cycle (cyclin D1 and cyclin E), apoptosis (activation of caspases and downregulation of antiapoptotic gene products), proliferation (HER-2, EGFR, and AP-1), survival (PI3K/AKT pathway), invasion (MMP-9 and adhesion molecules), angiogenesis (VEGF), metastasis (CXCR-4) and inflammation (NF-κB, TNF, IL-6, IL-1, COX-2, and 5-LOX) (Anand et al 2008;Wu et al 2011;Ahmad et al 2012). Green tea polyphenols suppresses class I histone deacetylases, and thus causes cell cycle arrest and apoptosis in prostate cancer (Thakur et al 2012).…”
Section: Polyphenolmentioning
confidence: 99%